Terminal Safety and Security as an Implication of Terminal Location and Accessibility, Mediated by Service Reliability: A Case Study at Tanah Merdeka Freight Terminal - Sigit Priebadi Widiansyah; Suripno Suripno; Zaenal Abidin; Djamal Subastian; Edhie Budi Setiawan (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to analyze the influence of terminal location and accessibility on safety/security through service reliability among logistics companies operating at Tanah Merdeka Terminal, North Jakarta. A quantitative approach was employed using a survey method. The study population consisted of approximately 40 logistics companies in the research area, all of which were included in the sample using saturated sampling technique. Data collection was conducted through questionnaire distribution between March and June 2025. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the assistance of SmartPLS version 4.1 software. The results indicate that service reliability has a significant influence on safety/security. Additionally, terminal location indirectly affects safety/security through service reliability. However, accessibility was found to have no significant direct or indirect effect on service reliability and safety/security. These findings highlight the critical role of enhancing service reliability as a key factor in improving logistics safety and security.